How restrictive laws affect the framing of the issues of corruption in Sudan - Hamid, Yassin Bashir; Mohammed, Rosli; Ahmed, Mohd Khirie (Global Society of Scientific Research and Researchers (GSSRR), 2018)
This study aims at identifying how the restrictive laws affect the Sudanese newspapers’ framing of the issues of corruption in Sudan. Therefore, the present study adopted a qualitative research method using in-depth interviews to adequately probe the perceptions of the Sudanese journalists and editors and explore how the restrictive laws affect the Sudanese newspapers’ in framing the issues of corruption in Sudan. A purposeful sampling was adopted in selecting 20 Sudanese journalists across both governmental and private newspapers operating in Sudan. In order to achieve clearer understandings of the journalists’ perspectives, the study adequately supported each theme with models generated by means of employing NVivo 8 software. The findings revealed that the Legislation is one of the key elements of the development of press industry by the Sudanese government through parliament to ensure press freedom. In addition, the Sudanese journalists indicate that the corporate ownership as well as market contexts are significant in determining the quality of information presented in the newspapers’ political news coverage. Hence, it can be concluded that there is a relationship between the newspaper ownership and the diversity of contents in newspapers. Consequently, there are negative effects of restrictive laws on the development of the Sudanese press industry in Sudan. Hence, the study calls for more attention towards the legislation's in Sudan to insure the press freedom and the good work environment for journalists to carry out their role in raising the Sudanese citizens’ awareness.